Method for preparing pure-phase and two-dimensional and three-dimensional blended-phase perovskite CsPbCl3 nanocrystals based on solution method

A solution phase method using hydrochloric acid and deionized water produces CsPbCl3 nanocrystals with uniform grain size and high light absorption, addressing the toxicity and performance issues of existing methods.

CN119118193APending Publication Date: 2024-12-13CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311920.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing solution phase methods for preparing perovskite nanocrystals are toxic, environmentally unfriendly, and lack control over nanocrystal grain size, leading to uneven performance and reduced light absorption.

Method used

A method using hydrochloric acid and deionized water as solvents, combined with lead acetate and cesium acetate, followed by filtration and drying in a tube furnace, to produce CsPbCl3 nanocrystals with controlled grain size and improved light absorption performance.

Benefits of technology

The method produces perovskite nanocrystals with uniform grain size, high light absorption, and low toxicity, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118193A_ABST
    Figure CN119118193A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing pure-phase and two-dimensional and three-dimensional blended-phase perovskite CsPbCl3 nanocrystals, which comprises the following steps: by taking hydrochloric acid and deionized water as solvents, weighing, stirring, carrying out suction filtration, drying and the like to prepare perovskite CsPbCl3 crystal powder. The method comprises the following steps: 1) weighing a certain amount of hydrochloric acid solution and deionized water; (2) slowly pouring lead acetate and cesium acetate solids into the solution in the step (1) in sequence; 3) fully stirring the solution, filtering, and cleaning with ethyl acetate to obtain perovskite nanocrystals; and 4) putting the product obtained in the step 3) into a tubular furnace, and drying in a dark place under a vacuum condition. The perovskite CsPbCl3 nanocrystal prepared by the preparation method disclosed by the invention is smooth in crystal grain, uniform in particle size, good in ultraviolet light absorption capability and relatively wide in spectral response range. The method can also be used for preparing various two-dimensional and three-dimensional perovskite nanocrystalline materials by a one-step method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Halogen perovskite nanocrystal materials have been proven in experiments to have advantages such as extremely strong light absorption efficiency, high fluorescence quantum efficiency and large defect tolerance. In addition, in terms of electricity, perovskite nanocrystals have excellent charge transport performance and are widely used in perovskite solar cells and photodetectors to improve film performance and optimize energy level arrangement. Therefore, perovskite nanocrystal materials have great commercial application prospects in the fields of optics and electricity.

[0002] The present invention provides a method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method, the method comprising: using hydrochloric acid as Cl - source, hydrochloric acid and deionized water as reaction solvents, and then lead acetate and cesium acetate were added successively as Pb 2+ and Cs + The source is added to hydrochloric acid and deionized water, and the nanocrystalline solution is obtained after sufficient stirring, and then filtered and washed with ethyl acetate, and the perovskite CsPbCl3 nanocrystalline powder is obtained after drying. The entire preparation process is carried out at room temperature.

[0003] At present, the mainstream methods for preparing perovskite nanocrystals include solution phase method, chemical vapor deposition method, emulsion method, etc. Among them, the solution phase method is the most commonly used method and the easiest method for large-scale production. The solution phase method is low-cost and easy to operate. The organic solvents generally used in the solution phase method are toxic and environmentally unfriendly. The perovskite nanocrystal powder prepared by other solution phase methods is also difficult to control its preparation process, resulting in problems such as uneven nanocrystal grain size and decreased light absorption performance.

[0004] Therefore, developing a method for preparing CsPbCl3 perovskite nanocrystals with low toxicity and good performance is an urgent problem to be solved. Summary of the invention

[0005] In order to prepare perovskite nanocrystals with better performance, the present invention provides a method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method.

[0006] The technical solution adopted by the present invention is as follows:

[0007] Step 1: Use deionized water, isopropanol and anhydrous ethanol to ultrasonically clean the filtration device, sample bottle and magnet used in the experiment, each for 10-15 minutes, and repeat twice. After the ultrasonic cleaning, put them in a drying oven for drying. After drying, use sealing film to seal the filtration device and sample bottle to prepare for the next step.

[0008] Step 2: Weigh appropriate amounts of cesium acetate (CH3COOCs) and lead acetate (CH3COOPb) in a glove box, weigh a certain amount of hydrochloric acid and deionized water at room temperature, and the mass ratio of hydrochloric acid, lead acetate and cesium acetate is: hydrochloric acid solution 0.01-50%, deionized water 0-50%, cesium acetate 0.01-60% and lead acetate 0.01-70%. Pour lead acetate into the hydrochloric acid solution and stir thoroughly for 10-15 minutes, and keep the magnetic speed at 100-300rpm. After the lead acetate is completely dissolved, slowly add cesium acetate, keep the solution pH value below 0-7 and slowly increase the speed to 600-900rpm. After the cesium acetate is completely dissolved, continue to stir the solution for 8-12 hours.

[0009] Step 3: Place a polytetrafluoroethylene filter membrane with a pore size of 0.1-0.4 μm into a suction filtration device and wet it with ethyl acetate. Pour the solution prepared in step 2 into the suction filtration device, place the filtered solid into a new sample bottle and pour in ethyl acetate, stir and wash for 10-15 minutes, repeat five times and store the obtained solid in the sample bottle. During the drying process, open the sample bottle cap and place the sample bottle in a tube furnace. The tube furnace is set to a temperature of 45-60°C, a heating rate of 3-9°C / min, and a heat preservation time of 24-48 hours. Finally, perovskite CsPbCl3 nanocrystals with good performance are obtained.

[0010] The present invention mainly adopts a solution method to prepare perovskite CsPbCl3 nanocrystals, using hydrochloric acid and deionized water as reaction solvents, and obtains perovskite CsPbCl3 nanocrystals through operations such as dissolution, stirring, suction filtration and tube furnace drying. The perovskite solution needs to be fully stirred for 8-12 hours, and the nanocrystalline powder is dried in a tube furnace at 45-60°C for 24-48 hours. The product of the present invention uses hydrochloric acid as Cl - source, hydrochloric acid and deionized water as reaction solvents, and then lead acetate and cesium acetate were added successively as Pb 2+ and Cs + The source is added to hydrochloric acid and deionized water, and the nanocrystal solution is obtained after sufficient stirring. Then, it is filtered and washed with ethyl acetate. After drying, the perovskite CsPbCl3 nanocrystal powder is obtained. The product has good optical properties. This method has simple experimental steps and strong controllability, and is suitable for large-scale preparation of perovskite CsPbCl3 nanocrystals. The temperature of the tube furnace is set at 45-60℃, the heating rate is 3-9℃ / min, and the insulation time is 24-48 hours. Finally, take out the sample and seal it for storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is an XRD characterization result diagram of the pure phase CsPbCl3 perovskite nanocrystal prepared in the present invention.

[0012] Figure 2It is an XRD characterization result diagram of the two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals prepared in the present invention.

[0013] Figure 3 This is a SEM characterization result diagram of the pure phase CsPbCl3 perovskite nanocrystal prepared in the present invention.

[0014] Figure 4 This is a SEM characterization result diagram of the two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals prepared in the present invention.

[0015] Figure 5 It is a UV-vis absorption spectrum characterization result diagram of the two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals prepared in the present invention.

[0016] Figure 6 It is a UV-vis absorption spectrum characterization result diagram of the pure phase CsPbCl3 perovskite nanocrystal prepared in the present invention.

[0017] Figure 7 It is a comparison chart of UV-vis absorption spectrum characterization results of pure phase CsPbCl3 perovskite nanocrystals prepared in the present invention and two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals prepared in the present invention.

[0018] Figure 8 This is a graph showing the band gap characterization results of the pure phase CsPbCl3 perovskite nanocrystals prepared in the present invention.

[0019] Fig. 9 This is a graph showing the results of the steady-state fluorescence emission spectrum characterization of the pure-phase CsPbCl3 perovskite nanocrystals prepared in the present invention.

[0020] Fig.10 This is a graph showing the FTIR characterization results of the CsPbCl3 perovskite nanocrystals prepared in the present invention.

[0021] Fig.11 The present invention is a whole experimental flow chart of preparing CsPbCl3 perovskite nanocrystals, including steps of weighing, dissolving, stirring, filtering, drying and the like. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with embodiments:

[0023] Example 1: Preparation of pure phase CsPbCl3 perovskite nanocrystals

[0024] (1-1) Cleaning before preparation

[0025] Prepare several sample bottles, a set of filtration devices and several magnetic particles, and use deionized water, isopropanol and anhydrous ethanol for ultrasonic cleaning, each for 10-15 minutes. After the ultrasonic cleaning, put the sample bottles, filtration devices and magnetic particles in a drying oven at 60°C for drying. After drying, seal the sample bottles, filtration devices and magnetic particles with sealing film, and store them in a drying oven at room temperature for use.

[0026] (1-2) Preparation of CsPbCl3 perovskite solution

[0027] Weigh hydrochloric acid (HCl) at room temperature, and weigh lead acetate (CH3COOPb) and cesium acetate (CH3COOCs) in a glove box. The mass ratio of the three is: 0.01-50% hydrochloric acid solution, 0-50% deionized water, 0.01-60% cesium acetate, and 0.01-70% lead acetate. Put a magnet into a sample bottle containing hydrochloric acid and place it on a magnetic stirrer for stirring at a speed of 100-300rpm. After the speed stabilizes, add lead acetate and stir for 10-15 minutes. After the lead acetate is completely dissolved, use a medicine spoon to slowly add cesium acetate to the solution. After the cesium acetate is completely added to the solution, slowly increase the speed to 600-900rpm and continue stirring for 8-12 hours.

[0028] (1-3) Preparation of CsPbCl3 perovskite nanocrystals

[0029] Prepare a suction filtration device, and place a polytetrafluoroethylene filter membrane with a pore size of 0.1-0.4 μm, and wet the filter membrane with a small amount of ethyl acetate. Pour the perovskite solution in (1-2) into the suction filtration device, place the filtered solid into a sample bottle and add excess ethyl acetate to ensure that the solid is completely submerged, then magnetically stir for 10-15 minutes, repeat the suction filtration and filtration 5-6 times, and then place the solid in a sample bottle for storage. Place the sample bottle opening in a tubular furnace, and evacuate the tubular furnace, keep the pressure display at -0.1 MPa, then introduce nitrogen to purge the tubular furnace until the pressure display remains at 0 MPa, repeat the vacuumization and nitrogen purge three times, and finally keep the vacuum in the tubular furnace, and keep the pressure display at -0.1 MPa.

[0030] (1-4) Characterization of products

[0031] The characterization spectrum of the pure phase CsPbCl3 perovskite nanocrystal prepared in the present invention is shown in the attached Figure 1 , 3, 6, 7, 8, 9, and 10. The XRD spectrum of the pure phase CsPbCl3 perovskite nanocrystals prepared in the present invention is completely consistent with the cubic phase CsPbCl3 standard card and has a higher peak intensity and a narrower half-height slit width, indicating that the prepared CsPbCl3 perovskite nanocrystals have a good degree of crystallization and are pure without impurity peaks, proving that cubic phase CsPbCl3 has been prepared. According to the SEM characterization diagram, it can be seen that the prepared nanocrystals have uniform grain size and smooth grain surface. According to the UV absorption visible light spectrum attached Figure 6 , 7 , indicating that the prepared nanocrystals have strong light absorption ability in the range of 200-600nm, and the absorption ability of ultraviolet light is most prominent. It has a wide light absorption range and intensity. According to the electron transition calculation formula, the band gap of the CsPbCl3 perovskite nanocrystal prepared by the present invention is 2.87eV, which is consistent with the theoretical optical band gap of 2.9eV. According to the attached Fig. 9 The steady-state fluorescence emission spectrum shows that the sample has a strong luminescence ability at 410nm, indicating that the sample has few defects and good luminescence performance. Fig.10 It can be seen that the sample does not contain organic matter through Fourier transform infrared spectroscopy (FTIR), indicating that the sample does not contain organic matter such as ethyl acetate.

[0032] Example 2: Preparation of two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals

[0033] (2-1) Cleaning work before preparation: Same as Example 1

[0034] (2-2) Preparation of two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite solution: A certain amount of deionized water is added to the hydrochloric acid solution, and the mass ratio of deionized water to hydrochloric acid is 0.1-1:1. Others are the same as in Example 1

[0035] (2-3) Preparation of two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals: Same as Example 1

[0036] (2-4) Characterization of products

[0037] The characterization spectra of the two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals prepared in Example 2 are shown in the attached figure. Figure 2 , 4 , 5, 7, and 10. According to the XRD spectrum, the two-dimensional and three-dimensional mixed phase CsPbCl3 perovskite nanocrystals added deionized water as a solvent, resulting in the appearance of a two-dimensional perovskite phase in the sample. Figure 4 This shows that the size of the formed grains is uniform, but there are many small and broken grains. The surface of the grains is relatively smooth, and many two-dimensional grains can be distinguished. Figure 5 and 7It can be seen that the light absorption range and intensity of the two-dimensional and three-dimensional mixed phase CsPbCl3 nanocrystals are relatively low, indicating the existence of two-dimensional perovskite CsPbCl3 grains. Fig.10 It can be seen that the final product does not contain any organic residue.

[0038] The above description is an embodiment of the present invention and does not limit the patent scope of the present invention. Any improvement or transformation using the contents of the present invention specification and its drawings, or direct or indirect application in other fields, still falls within the patent protection scope of the present invention.

Claims

1. A method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method, characterized in that: The following steps are involved: 1) mixing hydrochloric acid, deionized water, cesium acetate and lead acetate and stirring to obtain a mixture; 2) filtering and washing the mixture obtained in 1); 3) The washed product is placed in a tube furnace for heating and drying, and after cooling to room temperature, perovskite is obtained. CsPbCl3 nanocrystals.

2. A method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: In step 1), the hydrochloric acid, deionized water, cesium acetate and lead acetate are respectively in weight percentage: 0.01-50% of hydrochloric acid solution, 0-50% of deionized water, 0.01-60% of cesium acetate and 0.01-70% of lead acetate.

3. The method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: The hydrochloric acid, deionized water, cesium acetate and lead acetate are mixed and stirred, wherein the concentration of the hydrochloric acid is 37%. During the mixing, the lead acetate is quickly added to the hydrochloric acid, stirred for 10-15 minutes, and then the cesium acetate is slowly added after the lead acetate is completely dissolved. During the whole process, the pH value of the mixture is kept below 0-7.

4. The method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 2, characterized in that: Lead acetate and cesium acetate were weighed in an environment with a humidity lower than 0.01 ppm (in a glove box), and the other experimental operations of step 1) and step 2) were all carried out in air. According to claim 2, a method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method is characterized in that our lead acetate can be replaced by lead nitrate, lead iodide, lead propionate, lead butyrate, lead chloride and lead fluoride; our hydrochloric acid can be replaced by hydrochloric acid gas, hydroiodic acid, hydrobromic acid, etc.; The cesium acetate we use can be replaced by cesium iodide, cesium bromide, cesium chloride, cesium propionate, cesium butyrate, etc.

5. The method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: The sample bottles, sand core filtration devices and magnets used in step 1), step 2) and step 3) are ultrasonically cleaned for 15-20 minutes using deionized water, isopropanol and anhydrous ethanol in sequence.

6. The method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: Step 1) involves mixing hydrochloric acid and deionized water with lead acetate and cesium acetate. When adding lead acetate and cesium acetate to hydrochloric acid and deionized water, a magnetic stirring solution is used, and the rotation speed is maintained at 100-300 rpm.

7. The method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: Step 1) After slowly pouring in cesium acetate, the stirring speed of the solution is slowly increased from 100-300 rpm to 600-900 rpm, and the stirring is maintained for 8-12 hours.

8. The method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: In step 2), the solution used for the filtration is ethyl acetate, and the mixture is filtered 5-7 times using ethyl acetate. After the last filtration, the mixture is immersed in ethyl acetate and stirred for 10-15 minutes.

9. The method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: In step 3), after the sample is placed in the tube furnace, the tube furnace is purged with nitrogen for 5-7 times, and finally the tube furnace is evacuated, and the pressure reading is maintained at -0.1 MPa.

10. A method for preparing pure phase and two-dimensional and three-dimensional mixed phase perovskite CsPbCl3 nanocrystals based on a solution method according to claim 11, characterized in that: The tube furnace is vacuum dried, the temperature of the tube furnace is set at 45-60° C., the heating rate is 3-9° C. / min, and the insulation time is 24-48 hours.